THE ABSORPTION OF EUROPEAN FUNDS IN ROMANIA - Dragos Ionut ONESCU (International Journal of Research Science and Management, 2017)
Romania managed to stay with an extra 22.85 billion euros in all European funds after he paid the contribution to the EU budget in 2007 to date. The most difficult proved to attract structural funds and cohesion, absorption rate here is 61.5% in the period 2007-2013. In this paper, we propose to do an analysis the poor absorption of EU funds in Romania